2022
DOI: 10.1186/s12915-022-01228-z
|View full text |Cite
|
Sign up to set email alerts
|

The precedence effect in spatial hearing manifests in cortical neural population responses

Abstract: Background To localize sound sources accurately in a reverberant environment, human binaural hearing strongly favors analyzing the initial wave front of sounds. Behavioral studies of this “precedence effect” have so far largely been confined to human subjects, limiting the scope of complementary physiological approaches. Similarly, physiological studies have mostly looked at neural responses in the inferior colliculus, the main relay point between the inner ear and the auditory cortex, or used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 63 publications
0
10
0
Order By: Relevance
“…Why our rats exhibit much better ITD performance than that previously reported in biCI users is not yet clear, but possible explanations, some of which we have touched on above, include species differences, differences in the nature of the stimulation and/or training effects. It is difficult to completely rule out species differences, but this explanation nevertheless seems unlikely given the numerous studies that indicate that rats are a good animal model for human cochlear implantation [11; 63-69] and binaural hearing [11; 28; 29]. We were able to demonstrate that rats have excellent ITD sensitivity with thresholds very similar to those seen in other mammals [28], and exhibit a similar precedence effect, with strikingly similar temporal weighting functions to those seen in humans [29].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Why our rats exhibit much better ITD performance than that previously reported in biCI users is not yet clear, but possible explanations, some of which we have touched on above, include species differences, differences in the nature of the stimulation and/or training effects. It is difficult to completely rule out species differences, but this explanation nevertheless seems unlikely given the numerous studies that indicate that rats are a good animal model for human cochlear implantation [11; 63-69] and binaural hearing [11; 28; 29]. We were able to demonstrate that rats have excellent ITD sensitivity with thresholds very similar to those seen in other mammals [28], and exhibit a similar precedence effect, with strikingly similar temporal weighting functions to those seen in humans [29].…”
Section: Discussionmentioning
confidence: 99%
“…The fact that ITD discrimination is generally better for stimuli with rapid onsets rather than slowly rising envelopes is perhaps unsurprising given that, for normal hearing subjects, onset ITDs are normally the most salient [29; 30]. Electrophysiological studies of ITD sensitivity have similarly demonstrated the importance of onset cues in ITD sensitivity [29; 50; 51]. For example, in the inferior colliculus, ITD sensitivity may drop by 24-48% when onset responses are excluded from the analysis [50].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations